An overview of nursing and midwifery leadership, governance structures, and instruments in Africa - Faith Nawagi; Rosie Kneafsey; Mohammed Modber; Madeline Mukeshimana; Cecilia Ndungu; Lisa Bayliss-Pratt (BMC, 2023)
Abstract Background Investment in nursing and midwifery leadership and governance are key suggested approaches by the World Health Organization (WHO) Africa Regional Office to address the shortages in the nursing health workforce. However, there are few if any studies that have investigated the existence and operationalization of the nursing and midwifery leadership and governance structures in Africa. This paper fills this gap by, providing an overview of nursing and midwifery leadership, governance structures, and instruments in Africa. Methods We conducted a descriptive cross-sectional study of the nursing and midwifery leadership, structures, and instruments in 16 African countries using quantitative methodology. Data was analyzed using SPSS IBM 21 statistical software. Data was summarized in frequencies and percentages and presented as tables and charts. Results Only (9,56.25%) of the 16 countries included had retrievable evidence of all expected governance structures while (7, 43.75%) lacked one or more of the structures. A quarter (4, 25%) of the countries did not have a department of nursing and midwifery or chief nursing and midwifery officer at their Ministry of Health (MOH). The dominant gender representation across all the governance structures was female. Only Lesotho (1, 6.25%) had all expected nursing and midwifery governance instruments while the remaining (15, 93.75%) had either one or four of these instruments missing. Conclusions The lack of complete nursing and midwifery governance structures and instruments in various African countries is a matter of concern. Without these structures and instruments, the strategic direction and input of the nursing and midwifery profession cannot be maximized for the public good in relation to health outcomes. Addressing the existing gaps requires a multipronged approach with the need to strengthen regional collaboration, and advocacy, creating awareness, and advancing nursing and midwifery leadership training to enable nursing and midwifery governance capacity development in Africa.